2018
DOI: 10.18203/2349-2902.isj20181835
|View full text |Cite
|
Sign up to set email alerts
|

A study of clinical profile of hypospadias cases at a medical college hospital of South Gujarat, India

Abstract: Background: Hypospadias is a common congenital anomaly in which the anterior urethra is incompletely developed and does not extend to the tip of the glans penis. The present study was aimed to study clinical profile of hypospadias cases at a medical college hospital of southern Gujarat.Methods: This prospective study was conducted at a tertiary care hospital of South Gujarat, India including 32 patients of hypospadias. Data collected for each patient included age, sex, demography, and major symptoms, duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Similarly, Nyongole reports undescended testis as the only associated anomaly by 3.2% among patients with hypospadias; however, his study involved 63 patients about two-third of hypospadias patients in this study [15]. Similar findings have been reported in two other different studies at almost the same rate ranges [9,18]. There is no clear explanation to why the cryptorchidism is the most common associated anomalies, but this could be attributed to their pathogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, Nyongole reports undescended testis as the only associated anomaly by 3.2% among patients with hypospadias; however, his study involved 63 patients about two-third of hypospadias patients in this study [15]. Similar findings have been reported in two other different studies at almost the same rate ranges [9,18]. There is no clear explanation to why the cryptorchidism is the most common associated anomalies, but this could be attributed to their pathogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…16 Gohil et al found that 44 percent of hypospadias patients were under the age of five, with a mean age of presentation of 7.56 years. 17 In a study of 94 hypospadias children at BMC Hospital in Quetta, 61 percent were under the age of five, with a mean age of presentation of 6.7 years, and in another study of 304 hypospadias patients at Asopa Hospital in Agra, 62.5 percent were under the age of five. 18 According to the degree of hypospadias among the patients (N=60) in our study, the majority (46.7 percent) had distal hypospadias, followed by 30% with proximal hypospadias and 23% with mid hypospadias.…”
Section: Discussionmentioning
confidence: 97%